Rising Arsenic Level in Drinking Water: A Study of Schools and Local Areas of Multan, Pakistan - Zulfiqar, Muhammad Zohaib; Rao, Faiza; Rao, Anam; Raza Zaidi, Syeda Fizza (Scientific Inquiry and Review, 2023)
Water is the basic need for the survival of all living organisms; however, its contamination has caused disastrous effects on human health. Almost 80% of the total population in Pakistan is forced to use unsafe drinking water due to the scarcity of clean water sources. To assess, the risk involved and to monitor the amount of Arsenic and bacterial growth in drinking water, water samples were collected from different government schools and underdeveloped areas of Multan, Pakistan. Moreover, water samples were collected by randomly visiting areas and were sent for laboratory analysis to determine and detect the arsenic amount along with other parameters including aesthetic, physical, chemical, and bacteriological growth. The results indicated that all the data collected from Govt. schools and developed locality were having a large amount of arsenic in drinking water. A huge amount of Coliform growth was found in the Peer colony water, which indicated a highly unhealthy intensity of pollutant water for the population residing in this area. Therefore, urgent and regular monitoring of drinking water in Multan was required to prevent such contamination.